POSSIBILITIES OF USING OUTSOURCING IN THE PROVISION OF TRANSPORT AND LOGISTICS SERVICES - Kadyrov T.U. (American Journals, 2023)
This article highlights the importance of outsourcing in the provision of transport and logistics services, and systematizes the group of factors that encourage such activity. A method of evaluating the economic effectiveness of outsourcing and criteria for evaluating the description of the outsourcing's execution capabilities are proposed
Keywords: transport-logistics services, outsourcing, insourcing, outsourcer, insourcer, economic efficiency.